2021
DOI: 10.1177/0192513x211054471
|View full text |Cite
|
Sign up to set email alerts
|

Re-thinking Stepfathers’ Contributions: Fathers, Stepfathers, and Child Wellbeing

Abstract: Using data from a contemporary cohort of children, we revisit the question of whether children benefit from being close to and engaging in activities with a stepfather. We deploy the Fragile Families and Child Wellbeing Study, a birth cohort study of nearly 5000 children born in US cities in 1998–2000, with a large oversample of nonmarital births. We explore the relationships between stepfathers’ closeness and active engagement and youth’s internalizing and externalizing behaviors and school connectedness at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Findings from each of these East Asian samples highlight what might be thought of as deficiencies in single-father families including difficulties in creating the social resources that might be associated with mothers or women. These patterns are in sharp contrast to the U.S. samples, where adolescents in single-father families tend to do slightly better than those in single-mother families until income is controlled [ 2 , 3 , 4 ], and children tend to be exposed to equally involved parents regardless of parental sex [ 33 , 34 , 35 ]. Findings like these suggest that the conclusions from the U.S. data concerning how gendered parenting operates may not be universal, highlighting the need to examine cases beyond the Western context.…”
Section: Introductionmentioning
confidence: 77%
“…Findings from each of these East Asian samples highlight what might be thought of as deficiencies in single-father families including difficulties in creating the social resources that might be associated with mothers or women. These patterns are in sharp contrast to the U.S. samples, where adolescents in single-father families tend to do slightly better than those in single-mother families until income is controlled [ 2 , 3 , 4 ], and children tend to be exposed to equally involved parents regardless of parental sex [ 33 , 34 , 35 ]. Findings like these suggest that the conclusions from the U.S. data concerning how gendered parenting operates may not be universal, highlighting the need to examine cases beyond the Western context.…”
Section: Introductionmentioning
confidence: 77%
“…A small number of studies examined associations between stepparent–child relationships and child social outcomes. One study found that higher levels of stepfather–child relationship quality and stepfather involvement were associated with higher levels of adolescent children’s connection with peers at school (S. Gold & Edin, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…A substantial number of studies found significant associations between stepparent-child relationships and child psychological outcomes. In particular, studies found that higher levels of stepparent-child relationship quality were associated with children's lower levels of psychological distress (Falci, 2006;O'Connor et al, 2001); lower levels of stepfamily-related stress (Jensen et al, 2017); lower levels of anxiety (among female stepchildren in mother-stepfather families; Singleton-Winston, 2003); lower levels of internalizing problems or depression (S. Gold & Edin, 2021;Hodgetts, 2004;King, 2006;King et al, 2018;Miller, 2007;Suh et al, 2016;Willetts & Maroules, 2004); lower levels of loneliness (Hornstra et al, 2022); and higher levels of psychological adjustment (Leidy et al, 2011). Higher levels of stepparent-child conflict were also associated with higher levels of child internalizing problems over time and cross-sectionally (Fine et al, 1993;Little et al, 2019;Yuan & Hamilton, 2006).…”
Section: Literature Synthesis and Meta-analytic Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Repartnering provides a new opportunity to share economic resources, give and receive emotional support, and experience companionship and sexual intimacy, and thus may offset some of the negative consequences of divorce for adults and children (Amato 2010). Repartnered relationships may be more complicated or less "institutionalized" than first partnerships when it comes to rearing children (Cherlin and Furstenberg 1994), but recent research suggests that stepfather involvement may have changed in recent decades and may be more beneficial to children's well-being (Gold and Edin 2021).…”
Section: Repartneringmentioning
confidence: 99%